2003
DOI: 10.1081/lft-120017452
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Different Asphaltenes of Kuwaiti Origin

Abstract: Asphaltenes obtained by precipitation from crude Kuwaiti oils have been analyzed by proton magnetic resonance ( 1 H-NMR), carbon-13 nuclear magnetic resonance ( 13 C-NMR) and Infrared (IR) spectral techniques. The molecular weight and elemental analysis were also determined. These combined analytical data were used for the characterization of these Kuwaiti oils. The asphaltenes molecular weights range from approximately 4200-6500 with an H/C ratio of 0.91-1.1 with an average 45-71% aromatic carbons. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This small low MW portion seems to be underestimated in the light of the findings of Strausz and co-workers . The MW of the early eluting fractions is in good agreement with the studies of other groups on asphaltenes of a similar origen …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This small low MW portion seems to be underestimated in the light of the findings of Strausz and co-workers . The MW of the early eluting fractions is in good agreement with the studies of other groups on asphaltenes of a similar origen …”
Section: Resultssupporting
confidence: 87%
“…On the basis of average structural parameters derived from elemental analysis, MW determination, and NMR measurements, many researchers have proposed an average structure of an asphaltene molecule. ,, Some caution, however, should be applied while describing a structural diverse and in molecular size wide-spanning material like asphaltenes by only a single structure. Therefore, we think it is worthwhile to verify the structural homogeneity of the asphaltenes obtained from residual oils.…”
Section: Introductionmentioning
confidence: 99%
“…According to chemical structure, asphaltenes are aromatic polycyclic molecules surrounded and linked by aliphatic chains and heteroatoms (sulfur, nitrogen, oxygen) as well as traces of metal elements like nickel, iron, and vanadium. The chemical composition and structure of single asphaltene molecules can be assessed using different analytical techniques (Calemma et al 1995;Shirokoff et al 1997;Pekerar et al 1999;Bouhadda et al 2000;Buenrostro-Gonzalez et al 2002;Groenzin and Mullins 2000;Ancheyta et al 2002;Ibrahim et al 2003;Khan et al 2003;Avid et al 2004;Acevedo et al 2005;Siskin et al 2006). Elemental analysis, mass spectroscopy, and 1 H NMR can be used for determination of the average structural parameters such as the aromatic carbon ratio, the average number of alkyl side chains, and the degree of peripheral aromatic carbon substitution (Dereppe et al 1978;Dickinson 1980;Daaou et al 2008Daaou et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…NMR is a powerful analytical technique that can identify and quantify the aromatic and aliphatic carbons in the asphaltene molecule to understand asphaltene structure at a molecular level. Various research groups utilized NMR in asphaltene characterization. Ancheyta et al utilized the NMR to determine the most important structural parameters in asphaltene and reported that solvent type influences asphaltene composition. According to them, the aromaticity of asphaltene that is precipitated using n -heptane is higher than that obtained through n -pentane.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Seki and Kumata 24 and Hauser et al 25 reported an increase in aromaticity due to the shortening of alkyl side chains. Ibrahim et al 26 also used the NMR to characterize asphaltene derived from Kuwaiti crude oils and indicated that the molecules have between 5 and 9 polycondensed aromatic units that are attached by alkyl chains of 4−6 carbons. Hauser et al 27 recently utilized 1 H and 13 C NMR to obtain quantitative data (average structural parameters) about the structural composition of different vacuum residues and their thermally cracked products (i.e., cracked oil and pitch).…”
Section: Introductionmentioning
confidence: 99%